Influence of Heterointerfaces on the Kinetics of Oxygen Surface Exchange on Epitaxial La1.85Sr0.15CuO4 Thin Films - Gene Yang; So-Yeun Kim; Changhee Sohn; Jong K. Keum; Dongkyu Lee (Applied Sciences, 2021)
Considerable attention has been directed to understanding the influence of heterointerfaces between Ruddlesden–Popper (RP) phases and ABO3 perovskites on the kinetics of oxygen electrocatalysis at elevated temperatures. Here, we report the effect of heterointerfaces on the oxygen surface exchange kinetics by employing heteroepitaxial oxide thin films formed by decorating LaNiO3 (LNO) on La1.85Sr0.15CuO4 (LSCO) thin films. Regardless of LNO decoration, tensile in-plane strain on LSCO films does not change. The oxygen surface exchange coefficients (kchem) of LSCO films extracted from electrical conductivity relaxation curves significantly increase with partial decorations of LNO, whereas full LNO coverage leads to the reduction in the kchem of LSCO films. The activation energy for oxygen exchange in LSCO films significantly decreases with partial LNO decorations in contrast with the full coverage of LNO. Optical spectroscopy reveals the increased oxygen vacancies in the partially covered LSCO films relative to the undecorated LSCO film. We attribute the enhanced oxygen surface exchange kinetics of LSCO to the increased oxygen vacancies by creating the heterointerface between LSCO and LNO.